Das competências filosóficas como critério de avaliação no ensino da filosofia - Lira, Frank Wyllys Cabral (Brasil, 2021)
This work deals with school evaluation within the teaching of philosophy. The idea is to investigate and remedy a certain gap identified during practical and theoretical training itself as a licentiate in philosophy related to this topic. In this sense, as well as trying to delimit the scope of the investigation, the objective will be to investigate the philosophical competencies as an evaluation criterion in the teaching of philosophy for high school. Success in completing this objective will be achieved through qualitative, explanatory, and bibliographic research – using annotations – as well as through a step-by-step guided by some specific objectives - for example: introduce at an elementary level the notion of assessment or present a characterization of philosophy. It is concluded by the possibility of using philosophical competencies as an evaluation criterion, either by applying the two proposals identified in the literature or by the third proposal developed from the two previous ones.